1982
DOI: 10.1207/s15328023top0903_8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Performance on the GRE Advanced Psychology Test

Abstract: Academic factors, such as GPA, do contribute to GRE-P performance, but SAT scores contribute more, so is GRE-P a measure of achievement?The advanced Psychology test of the Graduate Record Examlnatron (GRE-P) IS a standardized test often used In conslderrng an applrcant for admlssron Into a graduate program In psychology Published research usrng thls test (Ewen 1969, Mehrabran, 1969 Strlcker & Huber 1967) has been dlrected at rdentlfylng ~t s ablllty to predrct success In graduate school Howlever, llttle empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nowaczyk and Frey (1982) suggested that these nonsignificant findings may have been due t o two methodological limitations. T h e three studies just mentioned examined overall undergraduate grade point average (GPA-U) a n d found n o significant relationship between GPA-U and GRE-P. T h e variables of grade point average for psychology courses (GPA-P) and t h e number of psychology course hours (HRS-P) completed before taking the GRE-P were also not significantly correlated with GRE-1'.…”
Section: Scores O N the Graduate Record Examination Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowaczyk and Frey (1982) suggested that these nonsignificant findings may have been due t o two methodological limitations. T h e three studies just mentioned examined overall undergraduate grade point average (GPA-U) a n d found n o significant relationship between GPA-U and GRE-P. T h e variables of grade point average for psychology courses (GPA-P) and t h e number of psychology course hours (HRS-P) completed before taking the GRE-P were also not significantly correlated with GRE-1'.…”
Section: Scores O N the Graduate Record Examination Subjectmentioning
confidence: 99%
“…In addition to determining the variables that affect GRE-P, Nowaczyk and Frey (1982) proposed two models (an Indirect model and a DirecdIndirect model) of how the variables of SAT, GPA-U, GPA-P, and HRS-P interact to affect CiRE-P. Assuming that these variables can be causally ordered (i.e., S A T can affect GPA-U, GPA-P, and GRE-P and that variables GPA-U, GPA-P, and HRS-P can affect GRE-P, but not vice versa), Nowaczyk and Frey tested the relative merits of the Indirect and Direct/Indirect models.…”
Section: Scores O N the Graduate Record Examination Subjectmentioning
confidence: 99%
See 1 more Smart Citation